Expression of toll-like receptors in non-endemic nasopharyngeal carcinoma - Ruuskanen M; Leivo I; Minn H; Vahlberg T; Haglund C; Hagstrom J; Irjala H (BMC, 2025)
Background
Nasopharyngeal carcinoma (NPC) is a malignant disease with an enigmatic etiology. NPC associates with Epstein-Barr virus (EBV) and human papillomaviruses (HPVs), while immunological factors also play a role in carcinogenesis. Toll-like receptors (TLRs) are pattern recognition receptors that participate in the immunological defence against pathogens, but their functions are also linked to cancer.
Methods
In our whole population-based study, we retrieved 150 Finnish NPC cases and studied their tumour samples for TLR1, TLR2, TLR4, TLR5, TLR7, and TLR9 expressions by immunohistochemistry, and for the presence of EBV and high-risk HPVs with EBV RNA and HPV E6/E7 mRNA in situ hybridizations. In addition, we analyzed the TLR expression patterns according to age, tumour histology, EBV/HPV status, and outcome.
Results
We found that all TLRs studied were highly expressed in NPC. Viral status of the tumours varied, and 62% of them were EBV-positive, 14% HPV-positive, and 24% virus-negative. The tumours with strong TLR2(nucl) or TLR5 expression were mostly virus-negative or HPV-positive keratinizing squamous cell carcinomas, and the patients with these tumours were significantly older than those with mild or negative TLR2(nucl)/TLR5 expression. In Kaplan-Meier analysis, the patients with strong TLR5 expression had worse survival compared to the patients with negative or mild TLR5 expression, but the results were linked to other patient and tumour characteristics. In multivariable-adjusted Cox regression analysis, the patients with positive TLR7 tumour expression had better overall survival than those with no TLR7 expression. The 5-year overall survival rates according to TLR7 expression were 66% (mild), 52% (moderate or strong), and 22% (negative).
Conclusions
TLRs are highly expressed in non-endemic NPC. Intensity of TLR2 and TLR5 expressions correlate with viral status, and TLR7 seems to be an independent prognostic factor of non-endemic NPC.